2020
DOI: 10.1002/adfm.202000503
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Non‐Noble Bifunctional Oxygen Electrocatalysts toward Large‐Scale Production

Abstract: The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are crucial reactions in energy conversion and storage systems including fuel cells, metal–air batteries, and electrolyzers. Developing low‐cost, high‐efficiency, and durable non‐noble bifunctional oxygen electrocatalysts is the key to the commercialization of these devices. Here, based on an in‐depth understanding of ORR/OER reaction mechanisms, recent advances in the development of non‐noble electrocatalysts for ORR/OER are reviewed. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
163
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(177 citation statements)
references
References 323 publications
(248 reference statements)
0
163
0
Order By: Relevance
“…[ 11,12 ] In addition, the introduction of transition metals into nitrogen‐doped carbon materials can further enhance the electrocatalytic ORR/OER activity of these catalyst. [ 13,14 ] For example, the introduction of iron can regulate the electronic structure of the catalyst so that the d‐band shrinks, and the electron density increases closer to the Fermi level. [ 15,16 ] This accelerates the electrons transfer to the reaction intermediates, making the Fe–N active site more prone to electrocatalytic oxygen reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[ 11,12 ] In addition, the introduction of transition metals into nitrogen‐doped carbon materials can further enhance the electrocatalytic ORR/OER activity of these catalyst. [ 13,14 ] For example, the introduction of iron can regulate the electronic structure of the catalyst so that the d‐band shrinks, and the electron density increases closer to the Fermi level. [ 15,16 ] This accelerates the electrons transfer to the reaction intermediates, making the Fe–N active site more prone to electrocatalytic oxygen reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, the activity of manganese oxides is usually inferior to that of precious metals. Strategies including doping, [37–39] introducing oxygen defects, [32,40,41] surface modification, [42] morphology tuning, [43,44] integration with other functional materials [34,45] have been developed for increasing the overall activity. Specifically, to improve the OER activity of manganese oxides, doping/co‐doping other transition metal elements (e. g., Co, Ni, Fe) [46,47] and integration of other non‐precious transition metal compounds (e. g., Co 3 O 4 ) [42,48] are effective strategies.…”
Section: Introductionmentioning
confidence: 99%
“…For further improving the ORR activity of manganese oxides, previous works indicated that introducing oxygen defects (or oxygen vacancies) in the crystal lattice of manganese oxides is an effective pathway for generating highly active, unsaturated Mn atoms as reactive sites [50,51] . Multiple strategies were proposed to induce oxygen defects on manganese oxides [41] . For example, some researchers induced oxygen defects without modification with other additives, e. g., heating manganese oxides under different temperatures and atmospheres, [52,53] and proton irradiation, [54] while some others created oxygen defects by electrochemical extraction of pre‐inserted cations from a Mn‐based crystal structure [32] .…”
Section: Introductionmentioning
confidence: 99%
“…There are many strategies for the preparation of transition metal electrocatalysts explored [14][15][16] since Jasinski [17] reported for the first time in 1964 that cobalt phthalocyanine exhibited oxygen reduction activity. In the realm of heterogeneous catalysis, nano-carbon materials (porous carbon, graphene, carbon nanotubes, carbon fibers) and non-metallic (N, P, S) doped nanocarbon materials are widely used as catalysts and catalyst carriers [18][19][20].…”
Section: Introductionmentioning
confidence: 99%